1988
DOI: 10.1002/app.1988.070350118
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane‐based sealants modified by blending with Kraft lignin

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Lignin samples contain different types and quantities of these functional groups that could beu t i l i z e di nm a k i n ga n d / o r replacing a majority of petroleum-based products in the manufacture of industrial biomaterials and biocomposites 6,7 such as polyurethanes. 8,9 Lignin incorporation in polyurethane production has been one of the most intensively investigated applications. 7À12 In some cases, its presence modifies the polyurethane cure rate by contributing aromatic groups and increasing the degree of crosslinking.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin samples contain different types and quantities of these functional groups that could beu t i l i z e di nm a k i n ga n d / o r replacing a majority of petroleum-based products in the manufacture of industrial biomaterials and biocomposites 6,7 such as polyurethanes. 8,9 Lignin incorporation in polyurethane production has been one of the most intensively investigated applications. 7À12 In some cases, its presence modifies the polyurethane cure rate by contributing aromatic groups and increasing the degree of crosslinking.…”
Section: ' Introductionmentioning
confidence: 99%
“…Lignin acts as a reinforcing agent, which adds rigidity to the polymeric matrix. 9 Several studies have suggested that the solubility and the uniformity of the lignin are the foremost key parameters affecting its reactivity for polyol substitution in polyurethane production. 12,13 This in turn is directly dependent upon different classes of hydroxyl groups that may be present in lignin causing both electronic and steric factors affecting the lignin reactivity 14 in the polyurethane network.…”
Section: ' Introductionmentioning
confidence: 99%
“…It is surmised that incorporation of lignin may contribute to an increase in the degree of crosslinking of PU. Further work in this initial series showed that the durability of the blended sealants, as measured by the change in mechanical properties of specimens subjected to natural and artillcial weathering programs, is generally neither hindered nor improved with the addition of lignin [1].…”
Section: Introductionmentioning
confidence: 97%
“…In previous papers the curing, and durability [1], morphology [2], miscibility [3], and swelling [4] characteristics of polyurethane (PU)-lignin polyblends were reported. Preliminary studies [1] indicated that the curing mode of PU sealants is modified with the addition of lignin, in that the initial setting time was reduced with the addition of lignin, but the rate of curing remained constant, indicating that the matrix hardens in direct proportion to the amount of lignin present in the blend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation